HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KELENTUKAN PERGELANGAN TANGAN TERHADAP KETEPATAN SHOOTING FREE THROW PADA EKSTRAKURIKULER BASKET SMP NEGERI 9 PEKANBARU - Muhibbal Jinan; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study was to determine the relationship between limb muscle explosive power and wrist flexibility on the ability to shoot free throws in the men's basketball team of SMP Negeri 9 Pekanbaru. The research was conducted in January – June 2021, with a sample of 12 students of SMPN 9 Pekanbaru. Prior to the analysis, a pree-test was first carried out with the average results. Based on the results of the research that the authors described in the previous chapter, the following conclusions can be drawn: 1) There is a relationship between the explosive power of the leg muscles and the accuracy of shooting free throws on the men's basketball team. SMP Negeri 9 Pekanbaru is 0.802 with a positive correlation and the level of the relationship is "very strong". 2) There is a relationship between wrist flexibility and the accuracy of shooting free throws in the men's basketball team of SMP Negeri 9 Pekanbaru of 0.865 with a positive correlation and the level of the relationship is "very strong". 3). There is a relationship between limb muscle explosive power and wrist flexibility on the accuracy of free throw shooting on the men's basketball team at SMP Negeri 9 Pekanbaru of 0.910 with a positive correlation and the level of the relationship is "very strong". Key Words: Limb Muscle Explosiveness, Wrist Flexibility Shooting Accuracy Free Throw